Pengaruh Ukuran Perusahaan, Pertumbuhan Penjualan dan Kepemilikan Institusional Terhadap Tax Avoidance - Novita Angie; Endah Finatariani (P3M Politeknik Negeri Bengkalis, 2025)
Tax avoidance remains a critical issue in corporate governance as it directly influences state revenue and reflects managerial decision-making. This study aims to analyze the effect of firm size, sales growth, and institutional ownership on tax avoidance in consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange during the 2019–2023 period. Using a quantitative research design, the study employed panel data regression with purposive sampling to select 14 companies, yielding 70 firm-year observations. Secondary data were obtained from audited annual financial reports. The results show that firm size has no significant effect on tax avoidance, indicating that company scale is not a determining factor in tax planning strategies. Sales growth has a negative and significant effect, suggesting that higher sales performance reduces the likelihood of tax avoidance practices. Meanwhile, institutional ownership does not significantly affect tax avoidance. These findings emphasize the importance of company performance in shaping tax behavior, while ownership structure and firm size play a limited role. The study implies that policymakers and stakeholders should consider growth dynamics when designing regulations and strategies to mitigate tax avoidance practices in the Indonesian market context.